2018
DOI: 10.1177/2280800018764763
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cells growing on perfused 3D collagen model produced higher reactive oxygen species level and were more resistant to cisplatin compared to the 2D model

Abstract: Introduction: Three-dimensional (3D) collagen scaffold models, due to their ability to mimic the tissue and organ structure in vivo, have received increasing interest in drug discovery and toxicity evaluation. Methods: In this study, we developed a perfused 3D model and studied cellular response to cytotoxic drugs in comparison with traditional 2D cell cultures as evaluated by cancer drug cisplatin. Results: Cancer cells grown in perfused 3D environments showed increased levels of reactive oxygen species (ROS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Again, a high concentration further increased the ROS production, whereas low concentrations (1 µM) diminished this effect, suggesting that the anti-and pro-oxidative activity of quercetin is concentration-dependent. Recently, it was demonstrated that 3D-grown cancer cells showed increased levels of ROS production, compared to 2D cultures, and that moderate ROS levels promote cell survival and proliferation [38,39]. Nrf-2 analysis revealed a concentration-dependent increase of Nrf2 reporter activity and corresponding transcriptional targets, SOD2, NQO1, GCLC, and HmMOX1, in MCM DLN spheroids when treated with quercetin for 24 h, compared to the control (Figure 6).…”
Section: Discussionmentioning
confidence: 93%
“…Again, a high concentration further increased the ROS production, whereas low concentrations (1 µM) diminished this effect, suggesting that the anti-and pro-oxidative activity of quercetin is concentration-dependent. Recently, it was demonstrated that 3D-grown cancer cells showed increased levels of ROS production, compared to 2D cultures, and that moderate ROS levels promote cell survival and proliferation [38,39]. Nrf-2 analysis revealed a concentration-dependent increase of Nrf2 reporter activity and corresponding transcriptional targets, SOD2, NQO1, GCLC, and HmMOX1, in MCM DLN spheroids when treated with quercetin for 24 h, compared to the control (Figure 6).…”
Section: Discussionmentioning
confidence: 93%
“… 80 For example, a recent study using organoids derived from human breast cancer showed higher levels of reactive oxygen species production and increased resistance to cisplatin compared with standard 2D cell cultures. 81 Importantly, organoids have been shown to exhibit different drug metabolism and secretion properties due to their different environmental cues, making them well suited for the study of drug therapies. 80 Because organoids more accurately represent human disease, they have tremendous potential for predicting in vivo drug sensitivity and responses.…”
Section: Personalized Medicine For Gc Patients Using Pdo Smentioning
confidence: 99%
“…We next compared the cytotoxicity of SLS between our new paper-based 3D cell culture platform and a commercialized 3D cell culture kit. In the commercially available 3D cell culture kit containing collagen-rich ECM, the cells grew into a circular form, 47,48 and on the paper-based 3D cell culture platform, the cells attached to and diffused across the surface in response to its topographical features (Fig. 4B).…”
Section: Comparison Of Toxicity Assessment In 2d and 3d Cell Culture ...mentioning
confidence: 99%